Android-Based Marriage Administration Information System at the Office of Religious Affairs, Lubuk Barumun District - Novrisyah Hasibuan; Raissa Amanda Putri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Office of Religious Affairs (KUA) Lubuk Barumun District is a government agency that carries out some of the duties of the Indonesian Ministry of Religion in the district in the field of Islamic religious affairs at the sub-district level. KUA Lubuk Barumun District can provide services in serving the community that will carry out marriage and reconciliation. The marriage administration and reconciliation process that is carried out is about submitting the marriage requirements file and filing the reconciliation requirements file. Based on field observations, the submission of the marriage and reconciliation requirements file is still done manually. At this time, the submission of the marriage and reconciliation requirements file still has to go to the KUA office first and then give the file to the Lubuk Barumun District KUA officer. This has resulted in registrants who live quite far from the KUA office in the Lubuk Barumun sub-district having difficulties because they have to pay extra for land transportation every time they visit the KUA office. Not only that, documents can accumulate so that the search for files, takes quite a long time. Based on these problems, an Android-based marriage administration information system was built to overcome them. Through this built system, the registrant submits the requirements file online and then the KUA Admin performs the verification stage after the file has passed the examination. so that it can make it easier for all parties from the prospective bride and groom to reconcile, the head of the KUA receives reports and computerized data collection media. The system development method used in this research is Rapid Application Development (RAD). With this android-based administrative information system, it can make it easier for KUA to produce information on the filing of marriage requirements and reconciliation in a more organized manner. Submission of information on registration and filing of marriage documents and referrals that are fast, precise, and accurate.